2002
DOI: 10.1038/sj.bjp.0704963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the selective inhibition of platelet thromboxane synthesis on the platelet‐subendothelium interaction

Abstract: 1 Drugs that inhibit TxA 2 synthesis are used to reduce platelet aggregation. The aim of this study was to compare the eects of a cyclo-oxygenase (COX) inhibitor (acetylsalicylic acid, ASA), a thromboxane synthetase (TxS) inhibitor (dazoxiben) and a dual TxS inhibitor and TxA 2 receptor blocker (DT-TX 30) on platelet aggregation and the platelet-subendothelium interaction in¯ow conditions. 2 The techniques used in this in vitro study were platelet aggregometry in whole blood, and measurement of platelet thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, controversial data regarding the effect of aspirin on platelet adhesion under flow conditions have been published. Several studies in which venous or arterial shear stress was evaluated showed no such effect (40, 41) or even increasing effects on platelet adhesion (42, 43), while others showed a moderate inhibitory effect of aspirin on platelet adhesion and thrombus formation (44–46). However, the models and shear rates used were different in the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversial data regarding the effect of aspirin on platelet adhesion under flow conditions have been published. Several studies in which venous or arterial shear stress was evaluated showed no such effect (40, 41) or even increasing effects on platelet adhesion (42, 43), while others showed a moderate inhibitory effect of aspirin on platelet adhesion and thrombus formation (44–46). However, the models and shear rates used were different in the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sarpogrelate was used at concentrations that inhibit aggregation of human and rat platelets (22), and aspirin was used at a concentration that inhibits aggregation of human platelets (23).…”
Section: Cell Culture and Experimental Protocol In Vitromentioning
confidence: 99%
“…However, 15,16-dihydrotanshinone had no effect in thrombin-activated platelets. This inhibitory effect of 15,16-dihydrotanshinone on TxA 2 was greater than that for aspirin (acetylsalicylic acid, 500 M), a well-known COX-1 inhibitor that leads to inhibition of synthesis of TxA 2 , PGE 2 and prostacyclin in human (De La Cruz et al, 2002). However, the discrepancy in the potencies for the inhibitory effects on platelet aggregation and thromboxane B 2 production appear to indicate that the antiplatelet activity of 15,16-dihydrotanshinone is ascribed only in part to the inhibition of TxA 2 production with the possible involvement of inhibition of thromboxaneindependent pathways for its antiplatelet activity.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, it seems likely that the inhibitory effect of 15,16-dihydrotanshinone I on phosphoinositide breakdown and the resulting decrease in [Ca 2+ ] i mobilization could in turn lead to a significant blockade of arachidonic acid liberation by PLC and cPLA 2 , which are the two main types of [Ca 2+ ] isensitive enzymes responsible for liberating arachidonic acid (Balsinde et al, 2002;Drayer et al, 1995). Arachidonic acid (AA), mainly released from the cell membrane phospholipid by phospholipase A 2 (PLA 2 ), is converted to various eicosanoids by cyclooxygenase (COX) and lipoxygenase (LO) (Kim et al, 2002), the COX-produced metabolites playing an fundamental role in the process of arterial thrombus formation (De La Cruz et al, 2002). 15,16-Dihydrotanshinone I inhibited collagen-induced arachidonic Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation